Management of patients with myocardial tuberculosis: A case series. (15th March 2021) - Dulin, Marie; Pasi, Nicoletta; Benali, Khadija; Ducrocq, Gregory; Roriz, Mélanie; Pellenc, Quentin; Para, Marylou; Chauveheid, Marie-Paule; Goulenok, Tiphaine; van Gysel, Damien; Dossier, Antoine; Papo, Thomas; et al.
Abstract: Background: Myocardial Tuberculosis (MT) is exceedingly rare. We aimed to report on myocardial involvement in tuberculosis (TB). Methods: All adult patients admitted in a department of Internal Medicine over an 8-year period with microbiologically proven MT were retrospectively reviewed. Demographic, medical history, laboratory, imaging, pathologic findings, treatment, and follow-up data were extracted from medical records. Results: Six patients (4 women, 37.6 [21.3–62.1] years) with MT were identified. MT included cardiac mass (n = 1), coronaritis (n = 1), left ventricle spontaneous rupture (n = 1) and myocarditis (n = 3). Pericardial effusion was associated with myocardial involvement in 2 cases. Four patients presented with acute heart failure. CRP serum level was high in all cases. The mean delay between the first symptoms and TB diagnosis was of 6 [1–44] months. The time from admission to diagnosis was of 18 (9–28) days. No patient had human immunodeficiency virus infection. Fluorodeoxyglucose - positron emission tomography (FDG-PET) detected extra-cardiac asymptomatic Mycobacterium tuberculosis infection localization and guided biopsy in 5 cases. As compared to TB patients without cardiac involvement, patients with MT were younger and more frequently women. All patients received antituberculosis therapy for 7.5 to 12 months associated with steroids for at least 6 weeks. Cardiac surgery was required in all but one patient. No patient died over a median follow-up of 1.2 [0.2–4.4] years. Conclusion: Our study emphasizes the clinical spectrum of life-threatening MT. Early diagnosis using FDG-PET imaging to target biopsy in extra-cardiac tissues and combined treatment strategy associating antituberculosis therapy, corticosteroids and surgery prevent complications and death. Highlights: Although exceedingly rare, myocardial tuberculosis may be life-threatening. FDG-PET is of great diagnosis value to guide biopsy of extra-cardiac tissues. Association of antituberculosis, steroids and surgery prevent complications and death.